Progress in Research on SARS-CoV-2 Infection Causing Neurological Diseases and Its Infection Mechanism - Wang, Lintao; Ren, Zhiguang; Ma, Li; Han, Yanjie; Wei, Wenqiang; Jiang, Enshe; Ji, Xin-Ying (Frontiers in Neurology, 2021)
COVID-19 has spread rapidly worldwide since its outbreak and has now become a major public health problem. More and more evidence indicates that SARS-CoV-2 may not only affect the respiratory system but also cause great harm to the central nervous system. Therefore, it is extremely important to explore in-depth the impact of SARS-CoV-2 infection on the nervous system. In this paper, the possible mechanisms of SARS-CoV-2 invading the central nervous system during COVID-19, and the neurological complications caused by SARS-CoV-2 infection were reviewed.